Nature and specifics in the recognition of faces and objects - Avramov, Ivan (Law Journal of New Bulgarian University, 2022)
Identification of persons is a method of collecting and verifying evidence, which establishes the identity between the persons presented for identification and those who are claimed in the testimony of the identifier. The main purpose of the identification is the collection of evidence and verification of existing ones, which can be done through the formed investigative versions. The identification, along with the inspection, search, seizure and investigative experiment as means of proof in criminal proceedings, is carried out in the presence of witnesses.